IMPLEMENTASI WEB SERVICE REST API UNTUK PENCARIAN RUJUKAN ISLAM MENGGUNAKAN ELASTICSEARCH - Fachrul Hakim; Nazruddin Safaat H; Lestari Handayani; Liza Afriyanti (Politeknik Bisnis Indonesia, 2024)
This study aims to develop a web-based search system for Islamic references using Elasticsearch, ExpressJS, and VueJS technology to facilitate access to valid religious information. During the data collection stage, the researcher gathered data from the Qur'an and 9 Hadith books in SQL file format. In the analysis and design stage, Elasticsearch technology was used for data search, ExpressJS for the backend providing the API, and VueJS for the frontend. Implementation involved configuring Elasticsearch and Logstash to process data in real-time. Testing was conducted using Black Box Testing, User Acceptance Test (UAT), and Postman to ensure system functionality. The results showed that the system operated well and received a score of 83% in the UAT, indicating it is suitable for use. This system enables efficient and valid searches for Islamic references, supporting better religious practices.